Mechanisms of Yangxin Tongmai Formula for blood stasis syndrome in coronary heart disease rats based on untargeted plasma metabolomics and intestinal flora 16S rRNA sequencing - Liu Yinxing; Chen Zijun; Wang Yiqin; Cheng Xihua; Li Jie; Chen Lingli (KeAi Communications Co., Ltd., 2023)
Objective: To investigate the correlations between intestinal flora, plasma metabolites, and blood stasis syndrome in coronary heart disease (CHD), and the mechanisms of Yangxin Tongmai Formula (养心通脉方, YXTMF) for blood stasis syndrome in CHD rats. Methods: A total of 18 specific pathogen free (SPF) male Sqrague-Dawley (SD) rats were used to establish CHD rat models with blood stasis syndrome, which were then randomized into model, YXTMF, and atorvastatin calcium (AVT) groups, with six rats in each group, and were intervened through gavage for two weeks. Subsequently, additional six rats that received normal diet were included as normal group. The pathological changes in the CHD rat models were identified by hematoxylin-eosin (HE) staining. The electrocardiogram, hemodynamics, and lipid profiles of the rats were detected as well. The untargeted plasma metabolomics of rats were analyzed by liquid chromotography-tandem mass spectrometry (LC-MS/MS), their ileal mucosal flora by 16S rRNA sequencing, and the correlation between the two results were also analyzed. Results: The whole blood viscosity, total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) of rats in the model group increased compared with those in the control group (P < 0.05). In the model group, the proliferation of endothelial cells in the coronary artery of rats was damaged, with quite a few vacuolated pathological changes observed. However, the endothelial lesions in the coronary artery of rats were alleviated in the intervention groups (YXTMF and AVT groups). With the use of LC-MS/MS, a total of 33 potential endogenous metabolites were identified in plasma, among which 1-methylhistidine, N-acetylhistamine, progesterone, and deoxycorticosterone were expected to be the differential metabolites in CHD rats with blood stasis syndrome. The 16S rRNA sequencing results showed that improved diversity and abundance of intestinal flora were observed in the YXTMF group. The correlation analysis suggested that Hydrogenophaga, Limnohabitans, and Polaromonas, which were highly related to the formation of blood stasis syndrome in CHD patients, were positively correlated with plasma metabolites such as 5-hydroxyindole, N-acetylhistamine, and progesterone (P < 0.01), but were negatively correlated with plasma metabolites such as L-arginine, homoarginine, and Boc-beta-cyano-L-alanine (P < 0.01). After YXTMF intervention, Lactobacillus, Corynebacterium, and Candidatus Nitrososphaera were positively correlated with plasma metabolites such as Boc-β-cyano-L-alanine, stachydrine, and naringenin (P < 0.05), while negatively correlated with 5-hydroxyindole, N-acetylhistamine, and oleoylethanolamide (P < 0.05). Conclusion: YXTMF could alleviate blood stasis syndrome in CHD rats through improving their plasma metabolisms achieved by regulating the intestinal flora.